A Case of Castleman's Lymphoma in Retroperitoneum Associated with Hypoferremic Anemia - KOJIMA, Miyuki; BESSHO, Fumio; HABU, Yuji; KAMOSHITA, Shigehiko; NAKAYAMA, Tsuguyo; YAMANAKA, Tatsuhiro (The Japanese Journal of Pediatric Hematology, 1989)
A case of Castleman's lymphoma in retroperitoneum associated with severe hypoferremic anemia is reported. A 15-year-old boy was admitted to our hospital for further examination of anemia, high level of CRP, and abdominal mass in November, 1987. Laboratory data indicated hypochromic microcytic anemia : (Hb 6.8 g/dl, MCV 53.6 fl, MCH 15.4 pg, Fe 10 g/dl, ferritin 18 ng/ml) Elevated erythrocyte sedimentation rate, high level of CRP over 10 mg/dl, and slight increase of serum IgG were also found. The anemia continued in spite of oral administration of 250 mg/day of ferrous sulfate. Abdominal palpation did not feel any mass but a solid mass was demonstrated in the anterior to the left kidney by abdominal ultrasonography and computed tomography. Angiography revealed a highly vascular mass but 67Ga-citrate scintigram failed to demonstrate abnormal uptake. On December 18, a mass measuring 4.0×3.5×3.0 cm was totally resected. It was an enlarged lymph node. Histologically, there were hyperplasia of lymphoid follicles and marked vascular proliferation with thick hyalinized walls. Interfollicular fibrosis and plasma cell infiltration were also shown in some areas. The histological picture was compatible with Castleman's lymphoma, an intermediate type of hyaline-vascular type and plasma-cell type. Anemia and other abnormal laboratory data were normalized after surgery and the patient remains well as of March, 1989.